(untitled) (Fountain Journal of Natural and Applied Sciences, 2023)
Variations in soil nutrients can influence the nutritional attributes of crops. Therefore, this study was conducted to evaluate the effects of varying sowing depths (2-8 cm) at 2 cm intervals on the nutritional contents of Luffa cylindrica (LC), Citrullus lanatus (CL) and Citrullus colocynthis (CC) fruits. Proximate, mineral and vitamin contents of seeds and pulps of fruits of the plants were determined. Protein (31.10±0.17 %), crude fibre (4.48±0.02 %), fat (47.13±0.27 %), ash (2.50±0.01 %) and carbohydrate (99.66±0.03 %) were higher (p<0.05) in seeds produced by CC sown at 6 cm compared with other sowing depths. Sodium (23.17±0.02 mg/100 g), potassium (370.47±0.34 mg/100 g), calcium (18.61±0.01 mg/100 g) and copper (0.25±0.01 mg/100 g) were higher in the pulp produced by seeds of LC sown at 6 cm. Similar significant increases were observed in phosphorus (13.28±0.11 mg/100 g), iron( 8.12±0.01 mg/100 g), zinc(8.60±0.06 mg/100 g), and magnesium (2.28±0.01 mg/100 g) in seeds produced by LC seeds sown at 6 cm. Vitamin A (0.58±0.01 mg/100 g) and Vitamin K(0.19±0.15 mg/100 g) were also higher in seeds produced by CL seeds sown at 2 cm, Vitamin C (7.76±0.05 mg/100 g) and vitamin E(0.17±0.00 mg/100 g)in the pulp of CL seeds sown at 4 cm while Vitamin D (1.40±1.33 mg/100 g) was higher in the pulp produced by CC fruits whose seeds were sown at 6 cm. In conclusion, seeds of CC sown at 6 cm contained higher proximate and mineral compositions and vitamins in pulp than CL and LC. Therefore, cultivation of the plants at 4-6 cm is recommended to ensure a higher nutritional content of the plants. Keywords: Luffa cylindrica, Citrullus lanatus, Citrullus colocynthis, proximate, vitamin